Keloid treatment assessment measures: A literature review - Alejandra Gutierrez; Anna Carmichael; Steven R. Feldman; Rithi John Chandy (Wiley, 2024)
Abstract Keloids are an exaggerated response to cutaneous trauma that has both a physical and psychological burden for patients. Keloids have high recurrence rates and are monitored years after treatment. There is currently no widely accepted assessment measure specifically for keloids. The purpose of this review was to compare available assessment measures for keloids. Eleven assessment measures were assessed based on validity, reliability, limitations, parameters, technological influence and feasibility. Only two assessment measures (Detroit Keloid Scale and the Keloid Area and Severity Index) were specific for keloids, easy to use, had no cost and were suitable for longitudinal use. These measures, in conjunction with quality of life measures such as the Dermatology Life Quality Index, could be used to provide a detailed and longitudinal assessment of keloid treatment.